Xung đột giữa công việc và cuộc sống riêng: Một nghiên cứu trong ngành y tế - Mai Thị Mỹ, Quyên; Lê Nguyễn, Hậu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The healthcare profession is characterized by the frequent occurrence of work interference with life (WLI) and life interference with work (LWI), which result in several negative consequences. This phenomenon has been investigated in prior studies, however, it was examined mainly under the common concept of work-life conflict (WLC). This study aims to elucidate the separate impact of WLI and LWI on the work and life of physicians. Employing a data set collected from 331 physicians in Ho Chi Minh City, structural model analysis shows that both WLI and LWI increase job stress. Compared to LWI, WLI causes a stronger increase in job stress and a stronger decrease in job engagement, although LWI represents the direct interference of life with work. As for personal life, WLI reduces mental health and damages physicians’ quality of life more than LWI. The theoretical and practical implications of the study were then discussed.